Attractiveness and body image : the mediating role of body mass index - Vogen, Christy Michelle (My University, 2002)
The purpose of this study was to examine the association between certain psychological and physical attributes and attractiveness in males and females. The psychological attributes studied included body-esteem, intelligence, and academic achievement. The physical attributes included body mass index (BMl) and the fluctuating asymmetry of 17 bilateral traits of the body. Seventy six female and 77 male undergraduate students from Lakehead University participated in the study. Pictures of the participants were taken (face, both head profiles, and full frontal profile), their hands were scanned, imprints of their feet were obtained, and their height and weight were measured. They also completed the Concerns about Shape and Weight Scale as a measure of body-esteem, and the Shipley Institute for Living Scale as an index of IQ. Sixteen raters evaluated participants' attractiveness from the facial and whole person pictures. BMI and body-esteem were correlated with attractiveness, with BMI being a much stronger correlate of attractiveness for females than for males. Also, females reported greater concerns about shape and weight. Finally, the relationship between attractiveness and body-esteem was mediated by BMI. These results do not replicate the Davis et al. (2001; 2000) studies where more facially attractive females had greater weight and shape concerns. This study supports the idea of a "looking glass self where our own self-perceptions reflect the perceptions of others about our appearance.
Keywords: Body image; Psychological correlates of attractiveness; Attractiveness and body image; Physical correlates of attractiveness